2018
DOI: 10.1080/00202967.2018.1424403
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment effect on structural and mechanical properties of Cr–C coatings

Abstract: In the present study, the effect of thermal treatment on the mechanical and structural properties of chromium carbide coatings with different thicknesses is evaluated. The coatings were deposited by cathodic magnetron sputtering on XC100 steel substrates. Samples were annealed in vacuum, at different temperatures ranging from 700 to 1000°C for 1 h, resulting in the formation of chromium carbides. X-ray diffraction (XRD), microanalysis X/energy-dispersive X-ray spectrometer (EDS), X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In earlier experiments (to be published elsewhere) we found that our CreN [12] and CreC [6] films show rather high friction coefficients between 0.53 and 0.62 and correspondingly high wear rates. Therefore, in this paper, our objective is to improve the coating's mechanical and tribological behaviour by increasing the carbon content.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…In earlier experiments (to be published elsewhere) we found that our CreN [12] and CreC [6] films show rather high friction coefficients between 0.53 and 0.62 and correspondingly high wear rates. Therefore, in this paper, our objective is to improve the coating's mechanical and tribological behaviour by increasing the carbon content.…”
Section: Introductionmentioning
confidence: 56%
“…On the other hand, the transformation of chromium nitrides to chromium carbonitrides in the coatings from 900°C consolidates the properties of carbides and nitrides, which can be explained by the smallest carbon atomic radius among the other elements (Cr, Fe, and N). Moreover, the activation energy for carbon diffusion in polycrystalline chromium is 1.14 eV and that of carbon into iron is about 1.4 eV [6,22]. These values are less than the activation energy of nitrogen into chromium.…”
Section: Crystalline Structurementioning
confidence: 86%
See 3 more Smart Citations